2009
DOI: 10.1063/1.3152764
|View full text |Cite
|
Sign up to set email alerts
|

High dielectric loss and its monotonic dependence of conducting-dominated multiwalled carbon nanotubes/silica nanocomposite on temperature ranging from 373 to 873 K in X-band

Abstract: The dielectric properties of multiwalled carbon nanotubes/silica (MWNTs/SiO2) nanocomposite with 10 wt % MWNTs are investigated in the temperature range of 373–873 K at frequencies between 8.2 and 12.4 GHz (X-band). MWNTs/SiO2 exhibits a high dielectric loss and a positive temperature coefficient (PTC) of dielectric effect that complex permittivity increases monotonically with increasing temperature. The PTC effect on the dielectric constant is ascribed to the decreased relaxation time of interface charge pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
121
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(127 citation statements)
references
References 27 publications
6
121
0
Order By: Relevance
“…In many cases, the import of SiO 2 can greatly improve the impedance matching of the as-prepared material toward the atmosphere, and thus showed that CNTs/SiO 2 composites possess excellent performances in different temperatures [40][41][42]. After coating with SiO 2 nanoshell, Fe/SiO 2 composites showed better microwave absorption property, as well as enhanced antioxidant capacity [43].…”
Section: A N U S C R I P Tmentioning
confidence: 97%
“…In many cases, the import of SiO 2 can greatly improve the impedance matching of the as-prepared material toward the atmosphere, and thus showed that CNTs/SiO 2 composites possess excellent performances in different temperatures [40][41][42]. After coating with SiO 2 nanoshell, Fe/SiO 2 composites showed better microwave absorption property, as well as enhanced antioxidant capacity [43].…”
Section: A N U S C R I P Tmentioning
confidence: 97%
“…It is apparent that the complex permittivity depends on temperature at all the measured frequency and it increases with rising temperature. This phenomenon could explain by Debye theory, and according to the Debye theory [34],…”
Section: Electromagnetic Properties Of Polyimide Nanocompositesmentioning
confidence: 99%
“…The thickness of all the samples was designed to 2.0 mm. The apparatus for high temperature test was similar to Ref [23]. In addition, the morphology of the nanocomposites was examined under a scanning electron microscope (SEM; JEOL JSM-5800 LV SKANNING).…”
Section: Characterizationmentioning
confidence: 99%
“…The broadening of the peak shows the spread of the relaxation with a relaxation time constant distribution. Furthermore, the appearance of peaks in M  provides a clear indication of the real dielectric relaxation process [32][33][34][35][36]. Figure 8 shows the complex modulus plots ( M  versus M  ) at various SM T .…”
Section: Electric Modulus Analysismentioning
confidence: 99%